Factors associated with dysfunction in menopausal women in Truong An ward, Hue city - Nguyen, Thi Huong Lam; Le, Dinh Hue; Nguyen, Thi Tan (Tạp chí Y Dược Huế, 2024)
Background: The study aimed to identify factors affecting dysfunction in the climacteric women. Materials and Methods: A cross-sectional descriptive study was carried out in 410 menopausal women in Truong An ward, Hue City. The degree of functional disorders in menopause was measured by Menopause Rating Scale (MRS). Yin deficiency and Yang deficiency constitutions were determined by Body Constitution Questionnaire. Results: The average scores of each sub-scale and total MRS scale were 3.05 ± 1.93, 4.70 ± 2.63, 3.12 ± 1.88, and 10.88 ± 5.72, respectively. Yin deficiency constitution accounted for 69.3% and Yang deficiency constitution 50.7%. The risk factors including: smoking with psychological (OR=9.75; 95% CI: 2.42-39.30; p<0.05); physical activity with urogenital (OR = 3.34; 95% CI: 1.42-7.85; p<0.05); parity with psychological (OR=1.45; 95% CI: 1.02-2.06; p<0.05); Yin deficiency constitution with psychological (OR=1.10; 95% CI: 1.06-1.13; p<0.001), somatovegetative (OR=1.23; 95% CI: 1.18-1.28; p<0.001), urogenital (OR=1.23; 95% CI: 1.15-1.32; p<0.001), and total scale (OR=1.31; 95% CI: 1.23-1.39; p<0.001); Yang deficiency constitution with psychological (OR=1.11; 95% CI: 1.08–1.14; p<0.001), somatovegetative (OR=1.09; 95% CI: 1.05–1.13; p<0.001), urogenital (OR=1.09; 95% CI: 1.03–1.15; p<0.05), and total scale (OR=1.17; 95% CI: 1.10–1.24; p<0.001). Conclusions: Smoking, physical activity, parity, Yin deficiency and Yang deficiency were factors associated with dysfunction in menopausal women.